Feature : A salty safety solution. (10th January 2018) - Wåhlin, Johan; Klein-Paste, Alex
Abstract: As the wintry months take their grip on the northern hemisphere, Johan Wåhlin and Alex Klein-Paste explain why salt keeps us safe on icy roads